Organs from deceased donors with false‐positive HIV screening tests: An unexpected benefit of the HOPE act. Issue 10 (23rd July 2018) - Durand, Christine M.; Halpern, Samantha E.; Bowring, Mary G.; Bismut, Gilad A.; Kusemiju, Oyinkansola T.; Doby, Brianna; Fernandez, Reinaldo E.; Kirby, Charles S.; Ostrander, Darin; Stock, Peter G.; Mehta, Shikha; Turgeon, Nicole A.; et al.
Abstract: Organs from deceased donors with suspected false‐positive HIV screening tests were generally discarded due to the chance that the test was truly positive. However, the HIV Organ Policy Equity (HOPE) Act now facilitates use of such organs for transplantation to HIV‐infected (HIV+) individuals. In the HOPE in Action trial, donors without a known HIV infection who unexpectedly tested positive for anti‐HIV antibody (Ab) or HIV nucleic acid test (NAT) were classified as suspected false‐positive donors. Between March 2016 and March 2018, 10 suspected false‐positive donors had organs recovered for transplant for 21 HIV + recipients (14 single‐kidney, 1 double‐kidney, 5 liver, 1 simultaneous liver‐kidney). Median donor age was 24 years; cause of death was trauma (n = 5), stroke (n = 4), and anoxia (n = 1); three donors were labeled Public Health Service increased infectious risk. Median kidney donor profile index was 30.5 (IQR 22‐58). Eight donors were HIV Ab+/NAT‐; two were HIV Ab‐/NAT+. All 10 suspected false‐positive donors were confirmed to be HIV‐noninfected. Given the false‐positive rates of approved assays used to screen > 20 000 deceased donors annually, we estimate 50‐100 HIV false‐positive donors per year. Organ transplantation from suspected HIV false‐positive donors is an unexpected benefit of the HOPE Act that provides another novel organ source. Abstract : Following the HOPE Act, organs from donors with false‐positive HIV tests are recognized as a novel resource that could help HIV‐infected individuals in need of organ transplants in the United States.